Does Mindfulness Correlate With Physical Function and Pain Intensity in Patients With Upper Extremity Illness?. (March 2018) - Beks, Reinier B.; Mellema, Jos J.; Menendez, Mariano E.; Chen, Neal C.; Ring, David; Vranceanu, Ana Maria
Background: Mindfulness skills training interventions seem efficacious in increasing physical function and decreasing pain intensity in patients with chronic pain. The relationship of mindfulness and upper extremity complaints in patients presenting to orthopedic surgical practices is not known. The aim of this study was to assess if mindfulness has a relationship to physical function and pain intensity in patients with upper extremity illness.Methods: In this cross-sectional study, a total of 126 patients with a nontraumatic upper extremity condition were asked to fill out questionnaires assessing the 5 facets of mindfulness, pain intensity, and upper extremity physical function, along with clinical and demographic variables prior to their visit with the surgeon.Results: Nonreactivity to inner experiences was the only facet of mindfulness that was correlated with upper extremity physical function and pain intensity. The overall mindfulness score was correlated with pain intensity only. In multivariable analyses, mindfulness was not associated with either physical function or with pain intensity. Pain interference was the most important predictor of both pain intensity and physical function.Conclusions: Greater overall mindfulness was associated with lower pain intensity, and greater ability to be nonreactive to inner experiences was associated with both pain intensity and upper extremity physical function in bivariate but not multivariable analyses. Pain interference was the most important predictor of both pain intensity and upper extremity physical function. Psychosocial interventions focused on improving physical function and decreasing pain intensity in this population should focus primarily on reducing pain interference, and secondarily on teaching patients mindfulness skills.